Risk Stratification after Biochemical Failure following Curative Treatment of Locally Advanced Prostate Cancer: Data from the TROG 96.01 Trial. (24th December 2012) - Steigler, Allison; Denham, James W.; Lamb, David S.; Spry, Nigel A.; Joseph, David; Matthews, John; Atkinson, Chris; Turner, Sandra; North, John; Christie, David; Tai, Keen-Hun; Wynne, Chris
Abstract : Purpose . Survival following biochemical failure is highly variable. Using a randomized trial dataset, we sought to define a risk stratification scheme in men with locally advanced prostate cancer (LAPC). Methods . The TROG 96.01 trial randomized 802 men with LAPC to radiation ± neoadjuvant androgen suppression therapy (AST) between 1996 and 2000. Ten-year follow-up data was used to develop three-tier post-biochemical failure risk stratification schemes based on cutpoints of time to biochemical failure (TTBF) and PSA doubling time (PSADT). Schemes were evaluated in univariable, competing risk models for prostate cancer-specific mortality. The performance was assessed by c-indices and internally validated by the simple bootstrap method. Performance rankings were compared in sensitivity analyses using multivariable models and variations in PSADT calculation. Results . 485 men developed biochemical failure. c-indices ranged between 0.630 and 0.730. The most discriminatory scheme had a high risk category defined by PSADT < 4 months or TTBF < 1 year and low risk category by PSADT > 9 months or TTBF > 3 years. Conclusion . TTBF and PSADT can be combined to define risk stratification schemes after biochemical failure in men with LAPC treated with short-term AST and radiotherapy. External validation, particularly in long-term AST and radiotherapy datasets, is necessary.